Teachers' reflective thinking in the context of their Gender, Experience, and School level - Joshi, Bharat (Vidyapith (વિદ્યાપીઠ), 2012)
In the field of teacher education, the concept of reflection is considered to be a critical element (Bain et al, 1999). Reflective teaching is very much essential for maintaining quality and achieving excellence. The present investigation intended to explore the reflective thinking of the teachers in the context of their Gender, Experience, and School Level. A sample of 579 Gujarati medium teachers (335 primary and 244 secondary school teachers) was selected from 50 primary and 22 secondary schools situated in Bhavnagar city. For the purpose of collecting data, Gujarati version of G. L. Taggart's Profile of Reflective Thinking Attributes (PRTA) was used. The three- way analysis of variance was applied for checking the significance of the main and interaction effects. The data were analyzed using the computer program SPSS. It was concluded from the results of the present investigation that the gender and experience of the teachers were not related with their reflective thinking.